CREEP ASSESSMENT OF REFORMER TUBE BY ULTRASONIC ATTENUATION AND MICROSTRUCTURE ANALYSIS - Faris, Muhamad Arif (IRC, 2016)
HK40 alloy tubing is commonly used in petroleum reforming facilities for its high temperature corrosion resistance. Unfortunately, the tubes can experience failure and rupture during service caused by formation of voids in tube wall by creep stress generated by the pressure differential, thermal gradient, excess temperature exposed between the inside and outside diameters of the tube. Routine creep monitoring and assessment of reformer tube is critical. Hence, it was required to assess the condition of tubes in avoid and prevent the failure. The degree of degradation can be assessed by monitoring microstructural changes which can be correlated with possible ultrasonic attenuation. The objective of the study is to assess creep damage based on ultrasonic attenuation and microstructural damage